1990
DOI: 10.1177/026921559000400404
|View full text |Cite
|
Sign up to set email alerts
|

The two-minute walking test: a sensitive index of mobility in the rehabilitation of elderly patients

Abstract: The usefulness of a timed walking test adapted for use as an index of mobility in elderly subjects undergoing rehabilitation was assessed. The 95% confidence interval for repeatability in 27 subjects was found to be -27% to +38%. The test was able to detect a significant improvement ( p < 0.01) in a group of subjects undergoing active rehabilitation, whereas no improvement was detected by a conventional rating scale. The two-minute walking test is a simple and sensitive index of mobility in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 6 publications
2
7
0
1
Order By: Relevance
“…The analysis of different gait clusters in e.g. the 2 min walk test [44] which includes more and longer straight walking bouts might be interesting to further confirm the findings of this study. The larger amount of strides in a 2 min test enables more force of expression when dividing strides in the non-constant gait clusters.…”
Section: Discussionsupporting
confidence: 71%
“…The analysis of different gait clusters in e.g. the 2 min walk test [44] which includes more and longer straight walking bouts might be interesting to further confirm the findings of this study. The larger amount of strides in a 2 min test enables more force of expression when dividing strides in the non-constant gait clusters.…”
Section: Discussionsupporting
confidence: 71%
“…It is a ratio measure, sensitive to change. In fact it was the only outcome measure to show improvement, confirming a recent study that found gait speed was more sensitive 25 to change than was a categorical measure.…”
Section: Outcome Measuressupporting
confidence: 77%
“…The 2-minute walk test is a variant of the 6-minute walk test which has been demonstrated to be a valid indicator of mobility amongst older rehabilitation patients. 23 Fear of falling was measured using the Activities specific Balance Confidence (ABC) Scale. 24 This scale asks participants to rate their confidence that they could complete each of 16 activities without losing their balance or becoming unsteady.…”
Section: Methodsmentioning
confidence: 99%